Proceedings of the 23rd ACM International Conference on Conference on Information and Knowledge Management 2014
DOI: 10.1145/2661829.2661966
|View full text |Cite
|
Sign up to set email alerts
|

A Word-Scale Probabilistic Latent Variable Model for Detecting Human Values

Abstract: This paper describes a probabilistic latent variable model that is designed to detect human values such as justice or freedom that a writer has sought to reflect or appeal to when participating in a public debate. The proposed model treats the words in a sentence as having been chosen based on specific values; values reflected by each sentence are then estimated by aggregating values associated with each word. The model can determine the human values for the word in light of the influence of the previous word.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…We note that LVM consistently yields higher recall than precision, whereas for SVM the opposite is true. These results are comparable to those reported in Takayama et al () for the value honor, the one category in those experiments that had a comparable number (317) of positive training examples.…”
Section: Preliminary Experimentssupporting
confidence: 89%
“…We note that LVM consistently yields higher recall than precision, whereas for SVM the opposite is true. These results are comparable to those reported in Takayama et al () for the value honor, the one category in those experiments that had a comparable number (317) of positive training examples.…”
Section: Preliminary Experimentssupporting
confidence: 89%
“…So far, we have only confirmed that our proposed method is applicable to the net neutrality corpus, however we have a plan to apply our method to another corpus that is related to different topic. Takayama et al [22] have achieved slightly but statistically significantly better method in terms of classification effectiveness (F 1 =0.7251 in 102-fold document crossvalidation for the net neutrality corpus), which is adopted a probabilistic latent variables model. We plan to explore other methods to see if we can generate a better values-dictionary.…”
Section: Discussionmentioning
confidence: 99%
“…Thus they improved SVM's effectiveness by expanding words features with associative words that extracted based on statistical similarity from unlabeled text and/or from hand-crafted thesaurus. In addition, there are several brand new approaches to model natural language text using probabilities [1], [10], [22]. However, these probabilistic approaches tend to focus on improving classification effectiveness in quantitative view.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be achieved at the word, phrase, sentence, multiple sentence, paragraph, or document level (Fleischmann et al, 2009). Takayama et al (2014) applied a word-scale probabilistic latent variable model for detecting human values, using a combination of literature on human values to annotate their training data, including a metainventory conducted by Cheng and Fleischmann (2010) for the purposes of easing automatic detection of human values in relation to Net Neutrality. Their resulting classifier achieves a level of accuracy similar to human annotators.…”
Section: Human Valuesmentioning
confidence: 99%